2017
DOI: 10.4209/aaqr.2017.04.0128
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Mortality and Hospital Admissions Attributed to Criteria Air Pollutants in Tehran Metropolis, Iran (2013-2016)

Abstract: Health impact assessments are useful for governmental authorities and decision-makers to determine the need for action and address potential public health problems arising from exposure to air pollution. The present study was conducted to assess the short-term health impacts of ambient air pollution in Tehran using the AirQ 2.2.3 model for March 2013-March 2016. Hourly concentrations of PM 10 , PM 2.5 , O 3 , NO 2 and SO 2 were acquired from the Department of Environment (DOE) and Tehran Air Quality Control Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…Hadei et al (2013) estimated short-term mortality attributable to various air pollutants. The total number of mortality cases attributable to PM 2.5 over the three-year period 2013-2016 was 4336 (Hadei et al, 2017b). In a study in Mashhad, the number of premature deaths due to short-term exposure to PM 2.5 was estimated to be 600 during the 2014-2015 period (Miri et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Hadei et al (2013) estimated short-term mortality attributable to various air pollutants. The total number of mortality cases attributable to PM 2.5 over the three-year period 2013-2016 was 4336 (Hadei et al, 2017b). In a study in Mashhad, the number of premature deaths due to short-term exposure to PM 2.5 was estimated to be 600 during the 2014-2015 period (Miri et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies show that high-level exposure to NO 2 in the air as a pollutant lead to increasing approximately 5-7% of the lung cancers among people (ex-smokers and non-smokers) 9 . Moreover, these studies reveal that a positive correlation between air pollutants such as NO 2 and adverse effects on human health such as changes in the kidney, liver, heart, and decrease resistance immunity to infectious diseases [10][11][12] . World Organization Health (WHO) reported that NO 2 associated with adverse effects such as increases in respiratory symptoms, asthma prevalence and incidence, cancer incidence, adverse birth outcomes and mortality 13 .…”
mentioning
confidence: 99%
“…These values were significantly lower than RRI values reported for Panama City [33], and lower than those reported in in Sao Paulo [25], in North Korea [26], in Chongqing, China [28], European cities [34], in Canadian cities [32], and in Temuco and Pudahuel, Chile [41]. When elderly people were considered, it was found that RRI values in MAM were comparable to those reported in Stockholm [38], in European cities [42], and in Tehran [43]. Basu et al [11] have used identical methods to assess the effect estimation through different US cities even with different ranges of apparent temperature.…”
Section: Discussionmentioning
confidence: 58%